Evolution of star formation in the UKIDSS Ultra Deep Survey field - I. Luminosity functions and cosmic star formation rate out to z=1.6 - Drake, AB; Simpson, C; Collins, C; James, P; Baldry, I; Ouchi, M; Jarvis, M; Bonfield, D; Ono, Y; Best, P; Dalton, G; Dunlop, J; et al. (Oxford University Press, 2013)
We present new results on the cosmic star formation history in the Subaru/XMM-Newton Deep Survey (SXDS)-Ultra Deep Survey (UDS) field out to z = 1.6. We compile narrowband data from the Subaru Telescope and the Visible and Infrared Survey Telescope forAstronomy (VISTA) in conjunction with broad-band data from the SXDS and UDS, to makea selection of 5725 emission-line galaxies in 12 redshift slices, spanning 10 Gyr of cosmictime. We determine photometric redshifts for the sample using 11-band photometry, and usea spectroscopically confirmed subset to fine tune the resultant redshift distribution. We usethe maximum-likelihood technique to determine luminosity functions in each redshift slice and model the selection effects inherent in any narrow-band selection statistically, to obviatethe retrospective corrections ordinarily required. The deep narrow-band data are sensitive tovery low star formation rates (SFRs), and allow an accurate evaluation of the faint end slopeof the Schechter function, α We find that a is particularly sensitive to the assumed faintest broad-band magnitude of a galaxy capable of hosting an emission line, and propose thatthis limit should be empirically motivated. For this analysis, we base our threshold on thelimiting observed equivalent widths of emission lines in the local Universe. We compute thecharacteristic SFR of galaxies in each redshift slice, and the integrated SFR density,ρ SFR. Wefind our results to be in good agreement with the literature and parametrize the evolution of the SFR density as ρ SFR α(1 + z)4.58 confirming a steep decline in star formation activity since z ~ 1.6. © 2013 The Authors Published by Oxford University Press on behalf of the Royal Astronomical Society.